Barnacle fouling in the Mediterranean sponges Axinella polypoides and Axinella verrucosa. (29th April 2013) - Haber, Markus; Gur, Amir; Blihoghe, Daniela; Ilan, Micha
Abstract Secondary metabolites protect many marine sponges (Phylum: Porifera) from settlement by fouling organisms. Previous studies on the subtidal demosponge Axinella verrucosa collected in the Western Mediterranean led to the isolation of compounds that inhibited the settlement of cyprids larvae of the intertidal barnacle Balanus amphitrite, and the enzyme chitinase, which plays a key role in the molting cycle of crustaceans. However, in a field survey conducted at three locations in Israel, Eastern Mediterranean Sea, we observed that A. verrucosa is fouled by the subtidal barnacle Balanus trigonus, a previously unknown association. Settlement inhibition assays using B. amphitrite with chemical extracts from Israeli A. verrucosa and Axinella polypoides, a sympatric, congeneric sponge that seems not to be fouled by B. trigonus, showed that cyprid larvae of B. amphitrite were inhibited by the extracts of both sponges from settlement at concentrations several magnitudes lower than natural volumetric extract concentration in the sponges. These results indicate that, unlike the intertidal barnacle B. amphitrite, the subtidal B. trigonus is unaffected by the compounds from A. verrucosa, stressing and underlining the importance of using suitable target organisms (i.e. from the same habitat) to test for ecologically relevant antifouling activities.